Using Situational Judgement Test to Assess The ‘Pancasila’ Student Profiles Construct: A Systematic Literature Review - Wahyuni, Tri; Rahayu, Wardani; Naga, Dali Santun (LPPM Universitas Negeri Jakarta, 2024)
The Situational Judgment Test (SJT) is very well known for measuring non-cognitive and non-academic attributes. Merdeka Curriculum contains the ‘Pancasila’ Student Profiles, those are global diversity, cooperation, critical reasoning, creativity and independence. This systematic literature review answers three basic questions, namely (1) in what fields is SJT used and for what purposes? (2) what dimensions in the Pancasila Student Profiles have been measured using the SJT method? , (3) how does technology influence the implementation of SJT? The Scopus database with the keyword Situational Judgment Test from 2013 to 2024 was explored and filtered using the PRISMA stages and measurement variables that were appropriate to the profile of Indonesian students. The results show that the medical sector uses SJT the most for student selection purposes. Indicators in the profile of Indonesian students namely collaboration, teamwork, empathy, cultural competence, understanding of ethnic diversity, decision-making skills, exploration, emotional management and emotional intelligence have appeared to be measured using the SJT method, and gamification, video and computer based test technology have been utilized in the implementation of SJT.